872 Consulting with children and parents to co-create resources about receiving paediatric outpatient parenteral antimicrobial therapy (OPAT). (17th August 2022) - Saron, Holly; Carter, Bernie; Munro, James; Young, Rob; Carrol, Enitan; Porter, David; Cantwell, Ruth; Crouch, Claire; Roberts, Julia
Abstract : Aims: We aim to showcase how we engaged with children and their parents via a teleconferencing platform (Zoom) using the power of illustration to trigger their recall of going home on outpatient parenteral antimicrobial therapy (OPAT). This co-creative consultation work was conducted to address the need, identified by children and parents in a previous research study, for enhanced preparation and information about OPAT. Methods: Children (n=4) who had received OPAT and their parents (n=4) were invited to participate by clinicians in the OPAT team at the children's tertiary centre. The children were sent specifically designed activity sheets asking them about their experiences in advance of an online activity consultation via Zoom. There was no set schedule for the online activity, instead conversation was triggered by the researchers asking the children about their drawings and responses in their completed activity sheets. Meanwhile, the illustrator listened, shared their screen, utilised the children's drawings and words and created new images that brought to life, in real-time, the experiences children and their parents shared. Children and their parents were in control of the process as they could direct, confirm or alter the drawings that appeared on the screen and ask for text to be added. Results: The freely available, co-developed resources include a 3-minute long animation ( figure 1 ) and an information leaflet ( figure 2 ), has been designed by and for children and their parents. Although remote engagement with children has become more commonplace, the use of real-time, co-creation based on children's illustrations and augmented by professional illustration and animation during the online activity is novel. The strengths (e.g. children enjoyed the approach) and limitations (e.g. reliance on stable Wi-Fi) of this approach have been explored. The findings from this consultation aligned with and added depth to understanding the experiences of children and parents about being at home on OPAT. Link to animation: https://www.youtube.com/watch?v=JERVuqmLLDM Link to information leaflet: https://figshare.edgehill.ac.uk/articles/figure/Things_you_might_like_to_know_about_having_your_medicine_at_home_information_leaflet_OPAT_/19180895/1 Conclusion: The COVID-19 pandemic has had a profound impact on the way consultation activities are conducted. This illustration driven, virtual consultation method with children receiving OPAT and their parents was successful and allowed the co-creation of free resources for other children and parents to use. Rather than constrain what was done, using virtual methods meant that children and their parents were able to engage with and co-create ideas for resources from the comfort of their own homes.